CORRECTED DETERMINATION OF SKIN DEPTH AT DIFFUSION OF THE PULSED MAGNETIC FIELD INTO MOVING CONDUCTING MEDIUM - Chemerys, V.T.; Raychenko, A.I. (Proceedings of National Aviation University (archive), 2005)
The theory of one-dimensional magnetic field penetration into conducting medium (flat plate) has been developed taking into account the motion of plate under the action of magnetic field at the linear growing of field intensity in the time on the external border of conductor. The process has been described by the equation of diffusion with convection term together with the equation of medium motion under the specific boundary conditions. The solution is obtained for the time interval in which the skin depth is less than thickness of plate. The depth of skin layer has increase in comparison with the classical case of immovable medium. This is a summarized effect of the field increase reduction on the medium surface and of the medium motion.